Pengaruh Waktu Pengerasan pada Kekuatan Paving Block yang Menggunakan Clay, Semen, dan Pasir. - Andius Dasa Putra; . Setyanto; Noor Syarifah Hasan (UNIVERSITAS LAMPUNG, 2013)
Soil samples were tested in this study are derived from Karang Anyar, South Lampung. Variationsin content of the mixture used were 6%, 8%, and 10% cement and 5% sand on every variation ofcement from 7 days, 14 days, and 28 days curing time as well as the burning treatment and no-burn combustion paving block samples. Based on the results of physical testing native soil, USCSsoil samples classify as fine-grained soil and included in the CL group.The results of this study is paving block that using clay, cement, and sand does not meet ISOpaving block. However, the addition of additives and curing can increase the physical and me-chanical properties of the soil. This is proved by the increasing value of the optimum moisturecontent and density of the mixture. For the compressive strength of paving blocks without and withburning process are best shown in the addition of a mixture of 10% with 28 days curing time